1999
DOI: 10.1007/s001250051203
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the sulphonylurea receptor gene: association of the exon 16-3t variant with Type II diabetes mellitus in Dutch Caucasians

Abstract: Type II (non-insulin-dependent) diabetes mellitus is a phenotypic and genetic heterogeneous disorder. Both defects in insulin action and insulin secretion are involved [1]. Mutations in a wide variety of genes, such as the genes for glucokinase, insulin receptor, hepatocyte nuclear factors and the mitochondrial DNA, contribute to deregulation of glucose homeostasis. One study has provided evidence for an association between two single nucleotide polymorphisms (SNPs) in the SUR1 gene and Type II diabetes in Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
36
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 9 publications
7
36
0
1
Order By: Relevance
“…The genotype and allele frequencies for the exon 16 polymorphism are presented in Table 1, next to the results of t Hart et al [1]. We could not detect a significant association between the t-allele of exon 16 and Type II diabetes mellitus in our cohort of patients (p = 0.31).…”
supporting
confidence: 51%
See 1 more Smart Citation
“…The genotype and allele frequencies for the exon 16 polymorphism are presented in Table 1, next to the results of t Hart et al [1]. We could not detect a significant association between the t-allele of exon 16 and Type II diabetes mellitus in our cohort of patients (p = 0.31).…”
supporting
confidence: 51%
“…Dear Sir, t Hart et al [1] analysed the association of two previously reported single nucleotide polymorphisms in the sulphonylurea receptor gene (SUR1) [2] with Type II (non-insulin-dependent) diabetes mellitus in the Netherlands [1]. They reported an association of the exon 16±3t variant with Type II diabetes mellitus by showing that the genotype frequencies between control subjects and Type II diabetic patients differed significantly (p < 0.05).…”
mentioning
confidence: 99%
“…Despite linkage disequilibrium between the variants, most studies found an association of either the exon 16 (intronic) variant (14,15) or the silent exon 18 variant (14,16,17) but not both. Furthermore, the allele associated with diabetes has been inconsistent (15).…”
Section: Sur1 Gck and Hnf1␣ Polymorphisms And Insulin Secretionmentioning
confidence: 98%
“…Despite linkage disequilibrium between the variants, most studies found an association of either the exon 16 (intronic) variant (14,15) or the silent exon 18 variant (14,16,17) but not both. Furthermore, the allele associated with diabetes has been inconsistent (15). No functional variant in the ABCC8 gene or in the adjacent KCNJ11 (KIR 6.2) subunit (14,17,31,32) has been identified to explain this association.…”
Section: Sur1 Gck and Hnf1␣ Polymorphisms And Insulin Secretionmentioning
confidence: 98%
“…The evidence for association of SUR1 polymorphisms is less clear, with a variety of results implicating an exon 16 polymorphism at the Ϫ3 position (12)(13)(14)(15), an exon 18 silent mutation (T759T) (12,16,17), and an exon 31 silent mutation (R1273R) (18) in type 2 diabetes. A subsequent meta-analysis of all published data concerning the exon 16 and exon 18 variants, however, yielded negative results (8).…”
mentioning
confidence: 99%